Patologia benigna de Mama: Incidencia de patología mamaria benigna - Solca años 1984 -1989 - Sánchez Sabando, Jaime; Plaza C., Jaime; Rivadeneira, Nery; Marengo B., Carlos (Revista Universidad de Guayaquil, 1990)
The purpose of this work is to establish the main benign breast diseases that are detected at the Solea Oncology Hospital, the form of presentation, the clinical characteristics and the treatment performed.